Divergência funcional em características reprodutivas, morfológicas e fisiológicas de Mabea fistulifera ao longo de um gradiente de altitude na Floresta Atlântica - Pereira, Jéssica Priscilla (2015)
This work aimed to study the ecophysiological performance matrices of Mabea fistulifera in response to changes in environmental conditions and availability of resources that occur along an elevation gradient of 535 m (399-934 m). The study was conducted in forest regeneration areas of the Atlantic Forest, characterized by vegetation type Forest Semideciduous in Caparaó-ES region. The identification and marking of 29 matrices occurred in October 2013, along with the collection of plant material. The morphological and physiological analyzes were carried out in March 2014, after the period of maximum vegetative growth. At the end of the reproductive period, fruits were collected for the determination of biometric features and germination performance. Matrices showed an average of 5 fruits per bunch and fruit with dry mass of 1.7 g. The seeds an average volume of 227.8 mm3 and dry weight of 83.3 mg. With the dry biomass of fruits partition, approximately 85% was partitioned in the pericarp and 15% partitioned to the seeds. Germination ranged 2-92%, while the germination speed index from 0.34 to 2.19. The fruits of biometrics and seeds were not associated directly with the altitude of establishment of headquarters. The germination performance (germination and vigor) was closely related to the proportion of dry biomass partitioned fruit for seed and showed a positive correlation with the change in altitude. The morphological and physiological characteristics were evaluated and related to altitude, nutrient availability in the soil (available phosphorus and sum of bases) and intrinsic factors of each plant matrix (Cup exposure index and stem diameter). Among the characteristics evaluated, the relationship between leaf area and xylem area active branches (morphology) and stomatal conductance (physiological), showed the highest variability between the arrays. Regions located at higher altitudes were associated with decreased availability of nutrients in the soil, and arrays that were established in these regions had higher specific leaf area values and leaf area ratio. M. fistulifera arrays presents phenotypic plasticity in morphological and physiological characteristics in response to changes in altitude, associated with changes in the availability of water and nutrients.